2013
DOI: 10.2478/amsc-2013-0088
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Flotation Kinetics Model for Triangular Distribution of Density Function of Flotability of Coal Particles / Weryfikacja Modelu Kinetyki Flotacji Dla Trójkątnego Rozkładu Funkcji Gęstości Flotowalności Ziaren Węgla

Abstract: Parameters of flotation kinetics model with a gamma and a triangular distribution have been determined based on the batch coal flotation experiments. Analyses were carried out at different values of the intensity of aeration air. The results of example analyses are presented in tables and graphs form. It follows from the carried out study on the mathematical models of flotability coefficient distribution of particles of examined coal samples that the triangular distribution model is statistical equivalent to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…On the basis of several works concerning the coal flotation process (Joostberens 2011;Kalinowski 1991;Kalinowski and Kaula 2000) it can be concluded that the dynamic of the flotation process for the SISO system may be represented by the model of the inertial element with a time delay. In this case, the flow intensity of a flotation reagent is the input signal U(s).…”
Section: Sensitivity Problems Of the Coal Flotation Process Control S...mentioning
confidence: 99%
“…On the basis of several works concerning the coal flotation process (Joostberens 2011;Kalinowski 1991;Kalinowski and Kaula 2000) it can be concluded that the dynamic of the flotation process for the SISO system may be represented by the model of the inertial element with a time delay. In this case, the flow intensity of a flotation reagent is the input signal U(s).…”
Section: Sensitivity Problems Of the Coal Flotation Process Control S...mentioning
confidence: 99%